2017
DOI: 10.1080/13880209.2017.1340965
|View full text |Cite
|
Sign up to set email alerts
|

Anti-fibrotic effects of Cuscuta chinensis with in vitro hepatic stellate cells and a thioacetamide-induced experimental rat model

Abstract: Context:Cuscuta chinensis Lam. (Convolvulaceae) has been used as a traditional herbal remedy for treating liver and kidney disorders.Objective: Anti-fibrotic effects of C. chinensis extract (CCE) in cellular and experimental animal models were investigated.Materials and methods: HSC-T6 cell viability, cell cycle and apoptosis were analysed using MTT assay, flow cytometry and Annexin V-FITC/PI staining techniques. Thioacetamide (TAA)-induced fibrosis model was established using Sprague Dawley rats (n = 10). Con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 43 publications
(41 reference statements)
0
6
0
Order By: Relevance
“…Sprague-Dawley rats were randomly divided into four groups (n=8) as follows: control group (CON), osteoporosis group (DEX), and 2 groups of rats with osteoporosis receiving 100 mg/kg CCE (DEX+CCE); the dose of CCE (100 mg/kg) was based on previous research (19) and our preliminary experiments. Rats in all groups except control group were injected with 7 mg/kg dexamethasone disodium phosphate intramuscularly once a week for five weeks (20).…”
Section: Methodsmentioning
confidence: 99%
“…Sprague-Dawley rats were randomly divided into four groups (n=8) as follows: control group (CON), osteoporosis group (DEX), and 2 groups of rats with osteoporosis receiving 100 mg/kg CCE (DEX+CCE); the dose of CCE (100 mg/kg) was based on previous research (19) and our preliminary experiments. Rats in all groups except control group were injected with 7 mg/kg dexamethasone disodium phosphate intramuscularly once a week for five weeks (20).…”
Section: Methodsmentioning
confidence: 99%
“…In a study by Kim et al ., to study the antifibrotic potential of Cuscuta chinensis extract on hepatic stellate cells and mouse models induced by thioacetamide, they found that the herbal extract reduced the expression of α-SMA, Col1α1 and TGF-β1 expression analyzed by RT-PCR. [ 21 ] Our study, in contrast, did not focus on the molecular aspects of fibrinogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Cornus officinalis Sieb is useful for bladder overactivity [ 17 ], erectile dysfunction [ 16 ], diabetes and diabetes-related chronic kidney disease [ 18 ]. Cuscuta chinensis Lam exhibits antioxidant [ 19 ] and anti-fibrotic effects [ 20 ]. Robus coreanus Miquel exhibits anti-inflammatory effects [ 21 ], is useful in erectile dysfunction [ 22 ] and increases sperm quality [ 23 ].…”
Section: Discussionmentioning
confidence: 99%